2018
DOI: 10.1038/s41598-018-19799-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction of 1-aminocyclopropane-1-carboxylate deaminase (ACCD)-producing endophytic Streptomyces sp. GMKU 336 towards salt-stress resistance of Oryza sativa L. cv. KDML105

Abstract: 1-aminocyclopropane-1-carboxylate deaminase (ACCD)-producing endophytic Streptomyces sp. GMKU 336 and its ACCD-deficient mutant were inoculated into Thai jasmine rice Khao Dok Mali 105 cultivar (Oryza sativa L. cv. KDML105) under salt stress (150 mM NaCl) conditions. The results clearly indicated that Streptomyces sp. GMKU 336 significantly increased plant growth, chlorophyll, proline, K+, Ca+, and water contents; but decreased ethylene, reactive oxygen species (ROS), Na+, and Na+/K+ ratio when compared to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 73 publications
3
63
0
Order By: Relevance
“…Jaemsaeng et al . () reported that endophytic Streptomyces sp. GMKU 336 enhances growth of rice ( Oryza sativa L. cv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaemsaeng et al . () reported that endophytic Streptomyces sp. GMKU 336 enhances growth of rice ( Oryza sativa L. cv.…”
Section: Resultsmentioning
confidence: 99%
“…which was used as a sole nitrogen source (Glick 2014). Jaemsaeng et al (2018) reported that endophytic Streptomyces sp. GMKU 336 enhances growth of rice (Oryza sativa L. cv.…”
Section: Expression Of Nit and Acds Genesmentioning
confidence: 99%
“…In this context, advanced molecular tools and technologies will facilitate the characterization of plant-microbe interactions and may expand our understanding. Protein and gene transcript studies can provide meaningful insights for describing the interactions of plants with beneficial microbes under stress conditions (Cheng et al, 2012;Singh et al, 2017;Jaemsaeng et al, 2018;Kumar et al, 2019). Investigating and analyzing the plant's root protein can provide a clear picture of the changes occurring at the time of microbe interaction.…”
Section: Introductionmentioning
confidence: 99%
“…We used 3,3′‐diaminobenzidine (DAB) staining to compare H 2 O 2 accumulation in the roots of V. radiata cv. CN72 inoculated with single bradyrhizobial strains (SUTN9–2 or DOA9) and co‐inoculation (SUTN9‐2:DOA9) (Figure A7; Jaemsaeng, Jantasuriyarat, & Thamchaipenet, ). The quantitative H 2 O 2 production was also measured in V. radiata CN72 roots using optical density (OD) measurement (compared with standard H 2 O 2 ; Yasuda et al, ).…”
Section: Resultsmentioning
confidence: 99%